OP0159 Microscopic Gut Inflammation in SPA is A Prognostic Factor for Initiation of Anti-TNF Therapy in Daily Practice. (10th June 2014) - Cypers, H.; Varkas, G.; Van Praet, L.; Van den Bosch, F.; Elewaut, D.
Abstract : Background: Microscopic gut inflammation frequently occurs in patients with spondyloarthritis (SpA), and is associated with a risk of evolution to Crohn's disease and ankylosing spondylitis (AS). Half of all SpA patients develop gut inflammation without associated gastro-intestinal symptoms. Two types of inflammation are seen: an acute type resembling infectious enterocolitis, and a chronic type, with features of early Crohn's disease. However, the relationship between gut inflammation and the need to initiate biologic therapy in SpA patients in daily clinical practice is not known. Objectives: To assess the association between the presence or absence of microscopic gut inflammation, and the independent decision of the treating rheumatologist to initiate anti-TNF therapy in newly diagnosed SpA patients, after 18 months of follow-up. Methods: The Ghent Inflammatory Arthritis and spoNdylitis cohorT (GIANT) is a prospective observational cohort study, following patients with a new diagnosis of axial or peripheral SpA, classified according to the ASAS criteria. Patients underwent an ileocolonoscopy at baseline to assess the presence of microscopic gut inflammation. None of the patients were on anti-TNF treatment at time of inclusion in the cohort. The decision to start anti-TNF therapy was made by the treating rheumatologist, who was unaware of gut histology. Results: In this analysis we included 63 patients who underwent ileocolonoscopy at baseline and had at least 18 months of clinical follow-up: 51 patients had axial SpA (23 AS and 28 non-radiographic axial SpA), and 12 patients had peripheral SpA. Gut histology was normal in 31 patients, but microscopic gut inflammation was found in 32 (acute/chronic). During the 18 months of follow up 27 (42, 9%) patients were started on anti-TNF therapy because of NSAID failure, BASDAI>4 and elevated CRP (national reimbursement criteria). Of the 31 patients with normal gut histology at baseline, 9 (29, 0%) started TNF-blocking agents. In patients with gut inflammation at baseline, a significantly higher proportion (18/32 i.e. 56, 2%) had been started on anti-TNF treatment (p=0, 042). In the chronic inflammatory subset, treatment was initiated in 12 out of 21 (57, 14%) patients, which was comparable to 6 out of 11 (54, 55%) patients in the acute subset. Higher CRP value and ASDAS at baseline were associated with the initiation of anti-TNF therapy as well, but this is probably influenced by current reimbursement criteria. Patients in whom anti-TNF was started also tended to have higher SPARCC values (MRI SIJ) at baseline, although this did not reach statistical significance (p=0, 069). BASDAI or BASMI at baseline were not significantly linked with start-up of anti-TNF therapy. There was also no significant difference between axial or peripheral SpA, nor between AS and nr-axSpA. Conclusions: SpA patients with microscopic gut inflammation, elevated CRP or elevated ASDAS at baseline were more likely to be given anti-TNF within 18 months of follow up in daily clinical practice. As we previously could not demonstrate any link between CRP and presence of microscopic gut inflammation in SpA, we anticipate that gut inflammation might be an independent prognostic factor that may be relevant for daily clinical practice. These data solidify the role of gut inflammation as an important driver of disease severity in SpA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4971